Keterampilan Menulis Karangan Persuasi Siswa Dalam Pembelajaran Think Talk Write dengan Media Poster - Octavia, Wilda Ayu Hajar; Satrijono, Hari; Hutama, Fajar Surya; Haidar, Dimas Abdi; Rukmana, Linda Purnamasari (EDUCARE: Journal of Primary Education, 2020)
Writing is a complex skill and is difficult for students to master well. This study aims to determine the effect of the application of Think Talk Write learning models with poster media on the writing skills of persuasion essay from fifth grade elementary school students. This type of research is a quasi-experimental design with a pre-test post-test control group. The sample in this study was VA and V class students of SDN Rambigundam 01 Jember. Collecting data in this study using interviews, tests, and documentation. The data analysis technique of student learning outcomes uses t-test. Based on the results of the t-test on the learning outcomes of students' persuasive essay writing skills, it is known that the value of tcount> ttable, (2.208> 2.0180), so it can be concluded that the hypothesis is accepted that the Think Talk Write learning model through poster media influences the writing skills of persuasion writing in the fifth grade students of SDN Rambigundam Jember 1. The results of the pretest and posttest activities also showed that the increase in the value of writing skills written by students in the experimental class was higher than the increase experienced by the control class. Difference in the increase in the average value experienced by the experimental class and control class by 3,7. Menulis merupakan salah satu keterampilan yang kompleks dan sulit dikuasai siswa dengan baik. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan model pembelajaran Think Talk Writedengan media poster terhadap keterampilan menulis karangan persuasi siswa kelas V SD. Jenis penelitian ini merupakan eksperimen semu dengan desainpre-test post-test control group. Sampel dalam penelitian ini adalah siswa kelas VA dan V B SDN Rambigundam 01 Jember. Pengumpulan data dalam penelitian ini menggunakan metode wawancara, tes, dan dokumentasi. Teknik analisisdata hasil belajar siswa menggunakan uji t-test. Berdasarkan hasil uji-t terhadap hasil belajar keterampilan menulis karangan persuasif siswa, diketahui bahwa nilai thitung>ttabel, (2,208>2,0180), sehingga dapat disimpulkan bahwa hipotesis diterima yaitu model pembelajaran Think Talk Write melalui media poster berpengaruh terhadap keterampilan menulis karangan persuasi pada siswa kelas V SDN Rambigundam 01 Jember. Hasil kegiatan pretest dan posttest juga menunjukan bahwa peningkatan nilai keterampilan menulis karangan siswa di kelas eksperimen lebih tinggi dari pada peningkatan yang dialami kelas kontrol. Selisih peningkatan rata-rata nilai yang dialami kelas eksperimen dan kelas kontrol sebesar 3,7.